Conditional and Synthetic Type IV Pili-Dependent Motility Phenotypes in Myxococcus xanthus - Subedi, Kalpana; Wall, Daniel (Frontiers in Microbiology, 2022)
Myxobacteria exhibit a variety of complex social behaviors that all depend on coordinated movement of cells on solid surfaces. The cooperative nature of cell movements is known as social (S)-motility. This system is powered by cycles of type IV pili (Tfp) extension and retraction. Exopolysaccharide (EPS) also serves as a matrix to hold cells together. Here, we characterized a new S-motility gene in Myxococcus xanthus. This mutant is temperature-sensitive (Ts–) for S-motility; however, Tfp and EPS are made. A 1 bp deletion was mapped to the MXAN_4099 locus and the gene was named sglS. Null mutations in sglS exhibit a synthetic enhanced phenotype with a null sglT mutation, a previously characterized S-motility gene that exhibits a similar Ts– phenotype. Our results suggest that SglS and SglT contribute toward Tfp function at high temperatures in redundant pathways. However, at low temperatures only one pathway is necessary for wild-type S-motility, while in the double mutant, motility is nearly abolished at low temperatures. Interestingly, the few cells that do move do so with a high reversal frequency. We suggest SglS and SglT play conditional roles facilitating Tfp retraction and hence motility in M. xanthus.